2015
DOI: 10.1007/s11695-015-1696-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Non-alcoholic Fatty Liver Disease and Steatohepatitis Risk Factors in Patients Undergoing Bariatric Surgery

Abstract: Age, waist circumference, serum ALT levels, and serum triglyceride levels are efficient and non-invasive predictive markers for the diagnosis and management of steatohepatitis in morbidly obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 43 publications
1
22
0
3
Order By: Relevance
“…Morita et al studied the prevalence of steatohepatitis and its predictive markers in patients with obesity undergoing bariatric surgery. They concluded that age, waist circumference, serum ALT and TG levels were the efficient non-invasive predictive markers to diagnose and manage steatohepatitis in patients with morbid obesity (33). There are various predicting or alarming factors for NASH in accordance to several studies.…”
Section: Discussionmentioning
confidence: 90%
“…Morita et al studied the prevalence of steatohepatitis and its predictive markers in patients with obesity undergoing bariatric surgery. They concluded that age, waist circumference, serum ALT and TG levels were the efficient non-invasive predictive markers to diagnose and manage steatohepatitis in patients with morbid obesity (33). There are various predicting or alarming factors for NASH in accordance to several studies.…”
Section: Discussionmentioning
confidence: 90%
“…10 However, Results from different studies show that the prevalence of NAFLD varies between 16.7% and 96% in morbidly obese patients subjected to bariatric surgery. [10][11][12][13][14][15][16][17][18][19][20][21][22] The wide range of NAFLD prevalence depends on the biochemical criteria and the method sensitivity used to detect NAFLD. 8,23 Furthermore, NASH, as a progressive manifestation of NAFLD, occurs in 7.3% to 98% of such patients.…”
Section: Prevalence Of Nafld and Nash In Bariatric Candidatesmentioning
confidence: 99%
“…It has been found that the prevalence of NAFLD was 84%, and noninvasive markers include the age, waist circumference, serum ALT activity, and serum triglyceride level are efficient for the diagnosis and management of NAFLD in morbidly obese patients [26].…”
Section: Bariatric Surgery the Liver And Insulin Insensitivitymentioning
confidence: 99%